Factors Affecting Radiation Exposure during Lumbar Epidural Steroid Injection: A Prospective Study in 759 Patients - Kim, Suyoung (Korean J Radiol, 2016)
OBJECTIVE: To estimate and compare radiation exposure and intervention time during lumbar epidural steroid injection (ESI) 1) under different practitioners and methods with continuous fluoroscopic monitoring, and 2) under one practitioner with different methods and monitoring. MATERIALS AND METHODS: We consecutively recruited 804 patients who underwent lumbar ESI and 759 patients who underwent 922 interventions were included for analysis in this investigation. Three different practitioners (a senior faculty member, junior faculty member, trainee) performed lumbar ESI using different methods (caudal, interlaminar, transforaminal). The senior faculty member performed lumbar ESI under two different methods of fluoroscopic monitoring (continuous [CM] and intermittent monitoring [IM]). The dose area product (DAP) fluoroscopy time, and intervention time during lumbar ESI were compared for 1) ESI methods and practitioners under CM, and 2) ESI methods and monitoring. RESULTS: With CM, interaction between the effects of the practitioner and the intervention on DAP was significant (p < 0.001), but not fluoroscopy time (p = 0.672) or intervention time (p = 0.852). The significant main effects included the practitioner and intervention on DAP, fluoroscopy time, and intervention time with CM (p < 0.001). DAPs and fluoroscopy time for caudal, interlaminar, and transforaminal ESI were higher with CM than with IM (p < 0.001). Intervention time did not differ between CM and IM. CONCLUSION: Radiation exposure is dependent on the practitioners and methods and within the established safety limits during lumbar ESIs under CM. With an experienced practitioner, IM leads to less radiation exposure than CM.